(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the effectiveness of positive discrimination measures (benefits, quotas, special state programs, and preferences) in the process of full integration of persons with disabilities into society. From the perspective of social equality and human rights, such measures are considered an important mechanism for promoting active participation of citizens with disabilities in education, employment, cultural activities, and civic life. The article also examines the legal foundations of positive discrimination, its practical implementation, its impact on the socialization process, and emerging challenges. Based on comparative analysis and empirical data, the efficacy of this approach in ensuring social justice is scientifically evaluated.